1988
DOI: 10.1093/nar/16.2.751
|View full text |Cite
|
Sign up to set email alerts
|

A laser Raman spectroscopic study of the interaction of calf-thymus DNA with Cu(II) and Pb(II) ions: metal ion binding and DNA conformational changes

Abstract: The interaction of calf-thymus DNA with Cu(II) and Pb(II) ions has been investigated in H2O and D2O solutions at physiological pH, using laser Raman spectroscopy. The results confirm the destabilizing effect of Cu2+ ions, which are shown to bind strongly to the guanine and cytidine bases, perturbing the A-T base pairs and disrupting the double-helical structure of DNA, whose conformation is markedly altered by these interactions. Earlier claims that Pb2+ ions destabilize DNA are not supported by the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 27 publications
2
77
1
Order By: Relevance
“…This peak is relatively insensitive to the conformation of the polynucleotide and many investigators have followed the suggestion of Tsuboi et al (9) that it be used as an internal standard in conformational studies. On the other hand, Raman studies of aqueous DNA solutions have shown that this band can be affected in intensity as well as in frequency when metal ions are present in the solution (10)(11)(12). Just how these changes are related to the extent and type of metal binding by the phosphate groups is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This peak is relatively insensitive to the conformation of the polynucleotide and many investigators have followed the suggestion of Tsuboi et al (9) that it be used as an internal standard in conformational studies. On the other hand, Raman studies of aqueous DNA solutions have shown that this band can be affected in intensity as well as in frequency when metal ions are present in the solution (10)(11)(12). Just how these changes are related to the extent and type of metal binding by the phosphate groups is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Duguid et al (1996) have observed similar results. The 784 cm −1 band is the composite of two major bands, one due to the cytosine ring breathing mode (Tajmir-Riahi et al, 1988) and the other due to phosphosiester symmetric stretching vibration (Dam et al, 2002). The cytosine vibration is sensitive to deputation exocyclic substitution while the phosphodiester vibration is less sensitive to deputation.…”
Section: Resultsmentioning
confidence: 99%
“…The values of the global relaxation time suggest also the existence of a vibrational relaxation time, because the reorientational movement is much more slower for the DNA macromolecule in aqueous solution. Particularly, the absence of reorientational broadening [13,[15][16][17], the cytosine ring breathing mode at 787 cm −1 [7,16,[18][19][20], the DNA backbone PO 2 − symmetric stretching vibration at 1094 cm −1 [12,16,19], the purines (dA, dG) and pyrimidines (dT, dC) residues band at 1376 cm −1 [17][18][19], the guanine (N-7) and adenine rings vibration at 1489 cm −1 [16,17] and the purines (dG, dA) 1578 cm −1 vibration ( [21] and references therein) of calf-thymus DNA, at different Mn 2+ ions concentrations, in the presence of Na + ions, are summarized in Tables 1, 2 and 4, 5, respectively.…”
Section: CM Muntean and I Bratu / (Sub)picosecond Dynamics In Mndnmentioning
confidence: 99%